2003
DOI: 10.1002/asi.10375
|View full text |Cite
|
Sign up to set email alerts
|

Reconfiguring control in library collection development: A conceptual framework for assessing the shift toward electronic collections

Abstract: Academic and special libraries are in the midst of a shift toward hybrid collections. This shift from collection ownership to an information access model supports the distributed nature of learning and work. However, unanticipated consequences of these changes are emerging. One confounding result is a visible pattern of discontinuities in collections, with unique features for electronic products. Patterns of discontinuities encountered included the occurrence of intermittent holes and unintentionally masked in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…In their 2008 survey on student use of e-books, Ebrary reported that 81 per cent of students would consider using e-books for their studies and research if there were more present and 63 per cent, if e-books collections contained more current content (Ebrary, 2008). Moreover, the frequency at which an electronic collection is updated and the proportion of current to non-current content will affect how patrons perceive the collection to be relevant to their needs (Covi and Cragin, 2004). Collections must be dynamic to support changes in both research and academic curricula (Covi and Cragin, 2004).…”
Section: Dynamic Collection Usage Analysismentioning
confidence: 99%
“…In their 2008 survey on student use of e-books, Ebrary reported that 81 per cent of students would consider using e-books for their studies and research if there were more present and 63 per cent, if e-books collections contained more current content (Ebrary, 2008). Moreover, the frequency at which an electronic collection is updated and the proportion of current to non-current content will affect how patrons perceive the collection to be relevant to their needs (Covi and Cragin, 2004). Collections must be dynamic to support changes in both research and academic curricula (Covi and Cragin, 2004).…”
Section: Dynamic Collection Usage Analysismentioning
confidence: 99%
“…Cette mouvance a permis d'évoluer du modèle de la propriété vers un nouveau modèle, celui du « anywhere, anytime access to information » (Covi & Cragin, 2004). Ce modèle implique de nouveaux dispositifs de dissémination du savoir, une diversification des canaux et surtout une omniprésence des bibliothèques.…”
Section: Resultsunclassified
“…168 Covi and Cragin discussed bundling of electronic resources, and factors that affect use or non-use and their implications LRTS 55 (4) for collection management. 169 Sullivan advised librarians to look at expectations and user needs of the "chip" generation and the functionality provided in electronic formats to try to find the best match. 170 In looking at OhioLINK consortium chemistry journals and collaborating with chemistry faculty, Feather, Bracken, and Diaz sought to balance costeffectiveness based on objective factors (such as price and usage data) with subjective factors (such as e-research value) to assess consortium collections.…”
Section: User-centered Assessmentmentioning
confidence: 99%